SPEECH ACT ANALYSIS OF DR. ZAKIR NAIK’S SPEECH ON YOUTUBE CHANNEL ENTITLED: DOES GOD EXIST - Nurbaeti Alawiyah; Iman Santoso (PROJECT (Professional Journal of English Education), 2020)
This research aimed to explore and identifying speech acts uttered by Dr. Zakir Naik in his standing dawah on the youtube channel entitled: Does God Exist. The research shows that factors of situation, place, topic, speaker, and context play an important role in analyzing speech act. The form of the speech has a representational function to inform and invite people. In this study, researchers used descriptive qualitative methods. The collect data, the writers used several steps. First, download the video on the internet. Second, transcript the dialogues into the texts. Third, reading the conversation texts. After that, identifying the sentences of Dr. Zakir Naik's speech. Then, counting the sentences includes a speech. And the last, describing the reason why the sentences include speech act. In which researchers examined naturally in every speech act that occurred in the theory stated by Yule (1996) in his theory about the types of speech acts divided into representative, directive, commissive, expressive, and declarative. In this study, the researchers found 13 utterances as a representative, 7 utterances as a directive, 2 utterances as a commissive, 2 utterances as a declarative, and not found expressive contained in the speech Dr. Zakir Naik's entitled: Does God Exist.